Regional influence of stratospheric processes in the formation of weather and climate of the Republic of Belarus employing monitoring data - Shlender, Timofey V.; Zhuchkevich, Veronika V.; Krasouski, Aliaksandr N. (Journal of the Belarusian State University. Geography and Geology, 2019)
The article aims at examining the latest trends in stratospheric processes, in particular, the differentiation of total ozone over the territory of the Republic of Belarus and their relationship with surface atmospheric circulation. As a result of the statistical analysis, the negative correlation link of total ozone and surface temperature, enabling to correct a mediumterm weather forecast, is confirmed. Furthermore, the fact of violation of the correlation between total ozone and the surface temperature during the springsummer ozone anomalies is revealed. The hypothesis of the influence of ozone mechanism on tropospheric circulation processes based on the specific case of the July hurricane of 2016 occurred over the territory of Belarus, is theoretically substantiated and practically illustrated. The hurricane has exemplified the partialeffect of the stratosphere on the troposphere, demonstrating the influence of jet streams and large gradients in the field of total ozone on a height of the tropopause. Thus, one has been positive to conclude that summer sharp changes in total ozone can lead to strong tropopause variations along with the appearance of powerful jet streams in the gap zones resulted in deterioration of the weather conditions in the lower troposphere.
Keywords: atmospheric circulation; stratospheric ozone; weather forecast; tropopause height; jet streams; stratospheric-tropospheric processes; ozone mechanism